Correlation between antibiotic consumption and bacterial resistance as quality indicator of proper use of these drugs in inpatients - Veličković-Radovanović Radmila M.; Petrović Jasmina; Kocić Branislava; Antić Snežana; Ranđelović Gordana (Vojnosanitetski Pregled)
Background/Aim. Antibiotics are the most frequently used medications in Serbian hospitalized patients. Information about antibiotic utilization and sensitivity among inpatients in Serbia is scanty, and there are no available publications on the topic. The aim of this study was to investigate the correlation between antibiotic use and bacterial resistance in the Clinical Center Niš, one of the biggest hospitals in Serbia. Methods. The data on antibiotics use in inpatients were obtained from the database of the Department of Pharmacotherapy and expressed as defined daily doses per 100 bed-days (DBD), during 2003-2007. Bacterial resistances were given as percentages of resistant isolates. Results. During the investigation period, the overall consumption of antibiotics had a significant decrease in 2007, by 22.99% (62.23 : 47.92 DBD; p < 0.05). The most frequently used antibiotics were cephalosporins, followed by penicillin's, aminoglycosides and quinolones. Hospital aminoglycosides consumption was reduced in 2007 to 59.9% (13.4 : 5.53 DBD) while the resistance to amikacin was reduced from 40.88% to 32.1%. However, utilization of ciprofloxacin had a significant increase in 2007 (120.7%). There was an alarming increase in the level of resistance to ciprofloxacin in our hospital (from 13.5% to 28.3 % in Escherichia coli and from 11.1 to 30.09% in Proteus mirabilis). Reduction of E coli resistant to amoxicillin+clavulanic acid correlated significantly with their utilization, while the resistance for all isolates decreased from 52.16% to 24.40%. Conclusions. These results confirm an association between the use of antibiotics and the prevalence of resistance. This methodology could provide good quality indicators of rational drug use and serve for local monitoring of antibiotics use and resistance, as well as for external comparison.